FLUVIAL GEOMORPHOLOGY - Jongkar, Grinang; edward, muol; Gabriel Tonga, Noweg; Anita, Muli; Mustafa Kamal, M.; Cindy, Peter; Hui-Ping, Chai; Wei-Seng, Lai; Nur Ezaimah, Idris; Hafida, Bolhen; Lee, Nyanti; Ling, Teck Yee; et al. (UNIMAS Publisher, 2024)
Physical characteristics of a stream is a crucial variable shaping biological communities and ecosystem functions. Therefore, fluvial geomorphological forms (landform, shape, size and networks) and processes (stream flow, sediment erosion, transport and deposition) have been central to ecological research in describing interrelationships between river. systems and their biodiversity. The topic, however, has not been emphasized in Borneo. The landscape of Sarawak is drained by 22 major river basins, with river basins displaying complex drainage networks.